Malaysia : Technical Assistance Report-Strengthening Outcome Based Budgeting. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance report reviews the reforms undertaken by the Government of Malaysia for strengthening outcome-based budgeting (OBB). OBB builds on the previous output-based modified budgeting system, which was in place for more than two decades. OBB aims to improve the efficiency, the performance, and the prioritization of expenditures by aligning national and ministerial outcomes with programs and budgetary resources and by integrating planning, budgeting, and evaluation. OBB has made good progress. The National Budget Office has assisted nine pilot ministries to redesign their program structure to link to outcomes and has plans to assist all ministries. There is an increased awareness in government of the importance of outcomes.